Affect and trust in educational migration of young people from provincial towns in Indonesia - Minza, Wenty Marina (Informa, 2022)
This study aims to understand trust and affect that are developed during young people’s educational migration from West Kalimantan to Yogyakarta, Indonesia. It further questions to what extent trust encourages migration and young migrants’ adaptation at the place of destination. In-depth interview and participant observation are utilised for gathering ethnographic data. Nine young people, between 19- and 26-years-old, were repeatedly interviewed for 20 months. This study found that young people’s education-related aspirations which later feed into their migratory experiences are motivated by relational affect of shared hope, and relational trust towards social networks. Hope can fluctuate, but its continuous nature often succeeds in maintaining educational aspirations and overcoming difficulties during the migratory process. Hope in others’ goodwill and intentions is the foundation of affect-based trust that is particularly grounded in supportive relationships. Together, relational affect and relational trust encourage young people to move and survive the challenges at the place of destination.